Dataset_PD_Rum_PSU_EI. - Arrivillaga, Christiane; Rey-Peña, Lourdes; Extremera-Pacheco, Natalio (Universidad de Málaga, 2024)
Background: Problematic smartphone use (PSU) is a public health issue that is currently rising among adoles- cents. The Compensatory Internet Use Theory (CIUT) poses that difficulties in handling negative life circum- stances could result in PSU. Furthermore, the Interaction of Person-Affect-Cognition-Execution (I-PACE) model suggests that the interaction between core characteristics and affective and cognitive responses could lead to PSU. The present study aimed to clarify the links between psychological distress and PSU by exploring rumi- nation as a mediator and emotional intelligence (EI) as a moderator. Methods: A sample of 1882 adolescents (54% female, 46% male) completed measures of psychological distress, rumination, EI and PSU. The PROCESS macro was used to conduct a moderated mediation analysis. Results: The mediation results showed a significant indirect effect from psychological distress to PSU through rumination. Furthermore, EI was a significant moderator of this effect. Thus, in adolescents with higher EI, the effect of psychological distress on PSU through rumination was not significant. Limitations: Cross-sectional data do not imply causality and further studies should use longitudinal designs. Self- report questionnaires may be susceptible to social desirability bias and future studies including other sources of information may help to minimize such bias. Conclusions: This study contributes to the field of problematic digital technology usage, showing that the link between psychological distress and PSU depends on the EI levels, which might influence PSU indirectly through rumination. Furthermore, empirical evidence for the CIUT and I-PACE models was provided. Lastly, in- terventions aiming at training EI may aid in the prevention of PSU.
Keywords: Adolescentes - Psicología; Madurez afectiva; Emociones; Redes sociales en internet - Aspectos psicológicos; Problematic smartphone use; Emotional intelligence; Rumination; Adolescents